2013
DOI: 10.1111/idh.12028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of chlorhexidine varnish and fluoride varnish on plaque Streptococcus mutans count – an in vivo study

Abstract: Cervitec varnish was found to be effective in reducing S. mutans count for a 3-month period, when compared to Duraphat varnish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
0
19
0
2
Order By: Relevance
“…The varnish did not significantly influence the growth of bacteria in the subgingival biofilm, especially the mutans streptococci were reduced after the application of the varnish. This is in accordance with other studies using varnishes with different concentrations of chlorhexidine but not with the study by Simoes Moraes et al . .…”
Section: Discussionmentioning
confidence: 99%
“…The varnish did not significantly influence the growth of bacteria in the subgingival biofilm, especially the mutans streptococci were reduced after the application of the varnish. This is in accordance with other studies using varnishes with different concentrations of chlorhexidine but not with the study by Simoes Moraes et al . .…”
Section: Discussionmentioning
confidence: 99%
“…Site-specific samplings of the emerging molars would have provided more detailed information on the local effects of the varnishes but such samples were not obtained in the present trial. However, a recent study has suggested short-term reductions of MS in dental plaque after intense applications of both a fluoride and a chlorhexidine varnish (Paul et al 2014), while Sajjan et al (2013) have published contrasting results. The only previous clinical comparison between the two products used in the present study displayed equal efficacy in the prevention of proximal caries in adolescents (Petersson et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…At dental hygienist visits, oral hygiene instructions were reinforced and the DH brushed patients' teeth. For Group C, Chlorhexidine varnish (FDA approved chemical adjuvant (1% chlorhexidine varnish 1% thymol -Cervitec Plus, Ivoclar Vivadent) 38,[53][54][55][56] was applied monthly by the DH to all available natural tooth surfaces. Chlorhexidine varnish was selected over fluoride varnish or silver nitrate since it also might help to reduce microbial burden, thereby improving periodontal health along with protecting against caries, 55,56 which is desirable for the elderly population.…”
Section: Methodsmentioning
confidence: 99%